Assessment of ICT tool usage in teaching Chemistry among secondary school teachers - Nafisat Oyebola Oyeniyi; Tawa Abiola Ahmed; Habibat Bolanle Abdulkareem (Curricula)
The study explored the availability and utilization of ICT tools for chemistry teaching in Offa Local Government Area (LGA) of Kwara State. The study employed a descriptive survey research design. Purposive sampling was adopted to choose twenty-one chemistry teachers from sixteen public senior secondary schools and five private senior secondary schools in Offa LGA for the study. The tool employed to obtain the data was a questionnaire that the researcher designed. The instrument was face-validated by senior lecturers in scientific education and Pearson's Product Moment Correlation Coefficient (PPMC). The study found that the minimal ICT resources available were only moderately used to teach chemistry and that public and private schools in Offa LGA, Kwara State, have some ICT resources. It was suggested that the government give sufficient ICT resources to public schools and that private school owners supply sufficient ICT resources to their schools. It was also suggested that chemistry teachers use ICT resources when instructing Chemistry.